Outcomes and Risk Factors for Mortality among Patients Treated with Carbapenems for Klebsiella spp. Bacteremia. - Lauren R Biehle; Jessica M Cottreau; David J Thompson; Rachel L Filipek; J Nicholas O'Donnell; Todd M Lasco; Monica V Mahoney; Elizabeth B Hirsch (PLoS ONE, 2015)
Extensive dissemination of carbapenemase-producing Enterobacteriaceae has led to increased resistance among Klebsiella species. Carbapenems are used as a last resort against resistant pathogens, but carbapenemase production can lead to therapy failure. Identification of risk factors for mortality and assessment of current susceptibility breakpoints are valuable for improving patient outcomes.The objective of this study was to evaluate outcomes and risk factors for mortality among patients treated with carbapenems for Klebsiella spp. bacteremia.Patients hospitalized between 2006 and 2012 with blood cultures positive for Klebsiella spp. who received ≥ 48 hours of carbapenem treatment within 72 hours of positive culture were included in this retrospective study. Patient data were retrieved from electronic medical records. Multivariate logistic regression was used to identify risk factors for 30-day hospital mortality.One hundred seven patients were included. The mean patient age was 61.5 years and the median APACHE II score was 13 ± 6.2. Overall, 30-day hospital mortality was 9.3%. After adjusting for confounding variables, 30-day mortality was associated with baseline APACHE II score (OR, 1.17; 95% CI, 1.01-1.35; P = 0.03), length of stay prior to index culture (OR, 1.03; 95% CI, 1.00-1.06; P = 0.04), and carbapenem non-susceptible (imipenem or meropenem MIC > 1 mg/L) infection (OR, 9.08; 95% CI, 1.17-70.51; P = 0.04).Baseline severity of illness and length of stay prior to culture were associated with 30-day mortality and should be considered when treating patients with Klebsiella bacteremia. These data support the change in carbapenem breakpoints for Klebsiella species.